Acute Recovery of Oral Word Production Following Stroke: Patterns of Performance as Predictors of Recovery - Cloutman, Lauren (IOS Press, 2009)
Background: Impairments in oral word production are common at the onset of stroke. The identification of factors that predict early recovery has important implications for identifying those at greater risk of continued impaired functioning, and the management of the patient's care following discharge. Aims: To identify patterns of performance that are predictors of acute recovery of oral word production abilities following stroke; to identify any association between early and more chronic recovery. Method and procedures:Acute stroke patients were administered oral word production tasks within 1–2 days of hospital admission, with repeat testing by 7 days; a subset of patients had repeat testing between three weeks to one year later. Performance was examined for error rate and type to identify potential predictors of early recovery. Outcome and results: The proportion of circumlocution and no response errors at initial testing were associated with the magnitude of recovery of language functioning within the first week following stroke. Patient characteristics of age and gender were found to have no influence on the degree of early recovery observed. None of the examined factors predicted late recovery. The degree of early recovery was not associated with the degree of later recovery. Conclusions: The current study identified patterns of task performance that increase our understanding of how oral word production recovers following acute stroke. The finding that the degree of early recovery does not predict the degree of later recovery is consistent with the hypothesis that early and late recovery are due to different mechanisms (restored blood flow in acute stroke, and reorganization in later recovery).